Factors affecting small scale fishermen's adaptation toward the impacts of climate change: reflections from Malaysian fishers - Abu Samah, Asnarulkhadi; Mohamed Shaffril, Hayrol Azril; Hamzah, Azimi; Abu Samah, Bahaman (Sage Publications, 2019)
This study aims to examine the influence of individual differences on the small-scale fishermen’s climate change adaptation practices toward climate change. This is a descriptive correlational study on 400 small-scale fishermen living in four climate change–affected areas in Malaysia, which were selected based on a multistage cluster sampling. In conclusion, it was found that age, income, and fishing experience recorded a significant relationship with climate change adaptation practices, whereas their household size did not yield any relationship with the adaptation practices. Furthermore, a number of small-scale fishermen who use fisheries technologies, have alternative jobs, and possess higher education have recorded better climate change adaptation practices compared with nonusers, full-timers, and less educated fishermen. Several recommendations were made to assist the concerned parties in developing better adaptation strategies that are fitted to the fishermen’s needs, interests, and abilities.